EVALUASI DAN UJI AKTIFITAS ANTIOKSIDAN KRIM SEDIANAN DARI DAUN NANGKA (Artocarpus heterophyllus Lam.) MENGGUNAKAN METODE DPPH - Sri Kartini; Roza Liana Sukma (Klinikal Sains : Jurnal Analis Kesehatan, 2026)
Jackfruit leaves (Artocarpus heterophyllus Lam.) are rich in bioactive compounds, including flavonoids, phenolics, tannins, and saponins, which exhibit antibacterial and antioxidant activities. These properties suggest their potential application as natural ingredients in anti-acne formulations. This study aimed to formulate an anti-acne cream containing ethanol extract of jackfruit leaves and to evaluate its physicochemical characteristics, including organoleptic properties, homogeneity, pH, and spreadability, as well as its antioxidant activity using the DPPH assay.The jackfruit leaf extract was obtained through maceration using 96% ethanol and incorporated into cream formulations at different concentrations (F0, F1, F2, and F3). The evaluation results demonstrated that all formulations possessed acceptable organoleptic characteristics, showed good homogeneity, maintained pH values within the skin-friendly range (4.5–6.5), and exhibited suitable spreadability values ranging from 5 to 7 cm. Antioxidant activity assessment revealed concentration-dependent effects, as indicated by the IC₅₀ values Formulations F0 (483.23 ppm and F1 (373.12 ppm) exhibited weak antioxidant activity, F2(156 .03 ppm)